Prevalência e fatores associados com as doenças sexualmente transmissíveis entre pacientes psiquiátricos no Brasil - Maria Rita Teixeira Dutra (2013)
Introduction: Sexually transmitted diseases are still highly prevalent worldwide and represent an important public health problem. Psychiatric patients are at increased risk of sexually transmitted diseases but there are scarce published studies with representative data among this population. Clinical and behavioral characteristics, besides social conditions, are the main factors associated with a higher vulnerability of this population. Objective: We sought to estimate the prevalence and correlates of self-reported sexually transmitted diseases, in a national representative sample, among patients with mental illnesses under care at psychiatric hospitals or CAPS, in Brazil, in 2006. Methods: This sample was drawn from a larger national multicenter cross-sectional study conducted in 11 public psychiatric hospitals and 15 public mental health outpatient clinics (CAPS) in Brazil in 2006, designed to assess risk behavior and sexually transmitted infections/HIV prevalence in a nationally representative sample of patients with chronic mental illnesses. The patients answered a semistructured questionnaire and only those participants that reported being sexually active at least once in life, were included (n=2145). Results: More than one quarter of the sample (25.8%) reported a lifetime history of sexually transmitted disease. Multivariate analyses showed that patients with a lifetime sexually transmitted disease history were older, had history of homelessness, used more alcohol and illicit drugs, suffered violence, perceived themselves to be at greater risk for HIV and had high risk sexual behavioral: practiced unprotected sex, started sexual life earlier, had more than ten partners, exchange money and/or drugs for sex and had a partner that refused to use condom. Conclusion: Our findings indicate a high prevalence of self-reported sexually transmitted diseases among psychiatric patients in Brazil and emphasize the need for implementing sexually transmitted diseases prevention programs in psychiatric settings, including screening, treatment, and behavioral modification interventions.